LEGAL ASPECTS OF GRANTİNG AND ENTRUSTİNG STATE GOVERNMENT TO THE LOCAL SELF GOVERNANCE - Khalilov, Gadir (Revista Gênero e Interdisciplinaridade, 2020)
The article includes provisions of local self-government. In this aspect, exceptional and entrusted powers of local self-government are distinguished. Both acts of international law and domestic legislation are in a mutual comparison. Differences in terminology between Constitution of the Azerbaijan Republic and municipal legislation are noted and appropriate legal unification is being recommended. Empowering of local governments with certain state powers - is one of the forms of interaction between public authorities and local self-government, softening the rigid organizational and competency dilution between the state and local government. To avoid the blurring of the constitutional model of local self-government, the issue of delegating powers to local authorities should be regulated in more detail.